Radiation Dose and Risk in Dental Panoramic Radiography: literature review - Elmorabit Naoual (EDP Sciences, 2021)
Aim: To review and search studies that evaluated the radiation doses and risks from dental panoramic radiography (DPR). This review may answer the following question “does panoramic dental radiation expose patients to health risks? Materiels and Methods: The search strategy was performed using the databases including GoogleScholar, PubMed, Science Direct and Nature from 2010 until september 2020. The search was limited to articles published in English. The 1031 titles that appeared, 15 fulfilled the criteria and were included in the review. Results: in 10 studies, the effective dose from DPRs was in the range of 5-49µSv, depending on the panoramic equipment used. The salivary glands received the highest absorbed doses (359-3044,3 μGy) and the thyroid gland absorbed doses were (40-250µGy). In terms of health risk, according to 5 studies, DPRs can induce genotoxic effects in oral epithelial cells and even induce cytotoxic effects leading to cell death. In 2 studies, women are at higher risk than men. The overall risk of cancer from radiation in children was more than adult. Conclusion: DPR can expose patient to health risks. It should only be applied when necessary, using radiation protection criteria.